Analysis of the Influence of Human Resource Management and Work Motivation on Employee Performance Through Organizational Commitment as Mediation (Analysis Study at The Industrial Development Job Training Center, Pasar Rebo, DKI Jakarta) - Bayu Setiawan, Muhammad; Antony, Antony; Khairul Amal, Muhammad (International Journal of Social Science, Education, Communication and Economics, 2024)
Research on Work Motivation on Employee Performance through Organizational Commitment as a mediator has been widely conducted, but there are still few Human Resource Management variables used as the parent variable. The purpose of this study is to analyze and explain the effect of human resource management and work motivation on employee performance mediated by organizational commitment. The research method used is quantitative. The population in this study were all civil servants and non-civil servants of PPKPI totaling 81. while the sample was taken using the census sampling method where the entire population was made a sample of 81 based on the overall population of PPKPI Pasar Rebo DKI Jakarta. The data collection method was carried out by distributing online questionnaires (google form) and offline (direct distribution to the field for those who had not filled out the google form). The analysis technique used was SEM PLS. The results of the study explain that Human Resource Management and work motivation have a positive and significant effect on Organizational Commitment, organizational commitment has a positive and significant effect on employee performance, human resource management has a positive and significant effect on employee performance, but work motivation has no effect and is not significant on employee performance. Human resource management and work motivation have a positive and significant effect on employee performance indirectly through organizational commitment as a mediator. The contribution of this study is to provide an overview to PPKPI Pasar Rebo DKI Jakarta employees in taking appropriate policies towards their employees, as well as to assist future researchers who will conduct similar research.